THE ROLE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN DEVELOPING MUSICAL CULTURE IN GENERAL EDUCATION SCHOOLS - Nuratdinova Almagul Bazarbay qizi (Journals Park Publishing, 2025)
Musical culture plays a vital role in shaping students’ aesthetic appreciation, emotional intelligence, and creative potential. In today’s globalized and rapidly digitized world, traditional music education methods are insufficient to fully engage students and meet their developmental needs. This article explores the role of innovative pedagogical technologies in fostering musical culture within general education schools. It highlights the integration of digital tools, interactive methods, and cross-disciplinary approaches, while also addressing challenges and future perspectives in adapting music education to contemporary realities.
Keywords: Innovative pedagogy, musical culture, music education, general education schools, digital technologies, creativity.